2020
DOI: 10.5005/jp-journals-10071-23649
|View full text |Cite
|
Sign up to set email alerts
|

R0 and Re of COVID-19: Can We Predict When the Pandemic Outbreak will be Contained?

Abstract: A bstract R 0 (R naught) is the basic reproduction number, also known as basic reproduction ratio or rate which is an epidemiological metric used to measure the transmissibility of infectious agents. R 0 is a derivative of the following variables—the duration of infectivity after the patient gets infected, the likelihood of transmission of infection per contact between a susceptible person and an infectious individual, and the contact rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 7 publications
2
59
0
Order By: Relevance
“…In this work, we used the extended Susceptible-Exposed-Removed (eSIR) compartmental model [22,23] to to the number of new infections generated by each infected person [16]. If R0 < 1, the disease will decline in the population, and if R0 > 1, the disease will spread faster [17]. However, foreseen risks include underestimation of the disease extend due to asymptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we used the extended Susceptible-Exposed-Removed (eSIR) compartmental model [22,23] to to the number of new infections generated by each infected person [16]. If R0 < 1, the disease will decline in the population, and if R0 > 1, the disease will spread faster [17]. However, foreseen risks include underestimation of the disease extend due to asymptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
“…R0 = β/γ is the basic reproduction number assuming the whole population is susceptible. The Markov chain Monte Carlo (MCMC) algorithm is used to implement this model and provide the posterior estimates and credible intervals of the unknown parameters, R0, β, and γ [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…As per his suggestion, if R0 < 1, the disease will perish in the population, and if R0 > 1, the disease will spread faster (Achaiah et al, 2020) . These calculations are as follows for countries that have successfully managed risk management.…”
Section: Sars-cov-2 Infection Prevention and Treatmentmentioning
confidence: 94%
“…R 0 is a measure of contagiousness of infectious agents, and it refers to the number of new infections generated by each infected person [ 18 ]. If R 0 < 1, the disease will decline spreading in the population, and if R 0 > 1, the disease will spread faster [ 19 ]. Moreover, compartmental models have long been used to model the dynamics of infectious diseases including influenza [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Markov chain Monte Carlo (MCMC) algorithm was used to implement this model in order to provide the posterior estimates and credible intervals of the unknown parameters, R 0 , β, and γ [ 19 , 25 ].  Previously, Mkhatshwa et al and Wangping et al reported that MCMC prior distributions can be initialized according to the SARS data from Hong Kong [ 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%